Analisis Sistem Penyimpanan Arsip Dinamis pada PT ASDP Indonesia Ferry (Persero) - Dinda Fitriyani; Christian Wiradendi Wolor; Adnan Kasofi (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This research was conducted at PT ASDP Indonesia Ferry (Persero) with the aim of determining the coding classification system for storing dynamic archives, obstacles, and solutions to the dynamic archive storage system. This research design uses descriptive qualitative research and a case study approach to provide a comprehensive picture of the manual archive storage system in the correspondence system. The unit of analysis in this study is employees in the Property and General Division, PT ASDP Indonesia Ferry (Persero) who often store dynamic archives manually which are archived in the archive warehouse. Data collection techniques are carried out using several methods including observation, interviews, and documentation. The results of this study indicate that the coding classification system for storing archives manually uses a system based on their respective divisions. For storing the archives, they are archived in the archive warehouse, namely the PGN Mas Warehouse and the BGR Warehouse, which are located very far from the head office, so that in storing the archives manually, there are obstacles, namely the difficulty of finding the archives again when the archives are needed. One solution to overcome these obstacles is by communicating between the archivist and the division that needs the letter and the archivist will make a simple index. Therefore, the results of this study are expected to be suggestions and input regarding the manual archive storage system in the correspondence system for future improvements.